Twitch interpolation: superimposed twitches decline progressively during a tetanic contraction of human adductor pollicis - Gandevia, S C (Blackwell Science Inc, 2013)
The assessment of voluntary activation of human muscles usually depends on measurement of the size of the twitch produced by an interpolated nerve or cortical stimulus. In many forms of fatiguing exercise the superimposed twitch increases and thus voluntary activation appears to decline. This is termed ‘central’ fatigue. Recent studies on isolated mouse muscle suggest that a peripheral mechanism related to intracellular calcium sensitivity increases interpolated twitches. To test whether this problem developed with human voluntary contractions we delivered maximal tetanic stimulation to the ulnar nerve (≥60 s at physiological motoneuronal frequencies, 30 and 15 Hz). During the tetani (at 30 Hz) in which the force declined by 42%, the absolute size of the twitches evoked by interpolated stimuli (delivered regularly or only in the last second of the tetanus) diminished progressively to less than 1%. With stimulation at 30 Hz, there was also a marked reduction in size and area of the interpolated compound muscle action potential (M wave). With a 15 Hz tetanus, a progressive decline in the interpolated twitch force also occurred (to ∼10%) but did so before the area of the interpolated M wave diminished. These results indicate that the increase in interpolated twitch size predicted from the mouse studies does not occur. Diminution in superimposed twitches occurred whether or not the M wave indicated marked impairment at sarcolemmal/t-tubular levels. Consequently, the increase in superimposed twitch, which is used to denote central fatigue in human fatiguing exercise, is likely to reflect low volitional drive to high-threshold motor units, which stop firing or are discharging at low frequencies.